Astragaloside II sensitizes human hepatocellular carcinoma cells to 5-fluorouracil via suppression of autophagy. (7th March 2017) - Wang, Meng; Huang, Can; Su, Yong; Yang, Cui; Xia, Quan; Xu, Du-juan
Abstract: Objectives: Inhibition of autophagy has been increasingly recognized as a potential therapeutic approach against cancer. Our previous reports showed that Astragaloside II improves hepatic cancer cells resistance by downregulating MDR1 and P-gp .The purpose of this study was to further investigated the effect of autophagy on AS-II reversing multidrug resistance and its molecular mechanism in hepatocellular carcinoma cells in vitro . Methods: Bel-7402 and Bel-7402/FU cell lines were used in this study. Western blot was used to detect the expression of autophagy-related protein, p-mTOR and p-p79s6k, MTT was used to analyse cell viability, GFP-LC3 punctate dots distribution was observed by GFP-LC3 transient transfection under fluorescence microscopy and silencing of autophagy-related genes was detected by small interfering RNA transfection. Key findings: Astragaloside II was able to significantly decrease the expression of LC3-II and Beclin-1 in a dose-dependent manner, Astragaloside II (80 μm ) further decreased LC3-II formation, Beclin-1 and GFP-LC3 puncta dots stimulated with 5-fluorouracil (0.2 mm ) in Bel-7402/FU cells ( P < 0.05). In addition, Astragaloside II is capable of sensitizing cells to 5-fluorouracil-induced cell death via inhibition of pro-survival autophagy involvement of MAPK-mTOR pathway. Conclusions: These findings suggested that Astragaloside II could suppress autophagy by interfering with Beclin-1 and LC3 via MAPK-mTOR pathway, through which sensitized human cancer resistant cells to 5-FU-induced cell death.